Elitna množična kultura - Štrajn, Darko (Monitor ISH, 2006)
Art festivals are intrinsic to the very concept of a city. In the age of globalisation, even local events may attain international dimensions due to the performers or the audience, or simply to the media interest in novelty. Some festivals appear to be firmly established on top of a festival hierarchy, unwilling to relinquish their privileged positions to other cities. Obviously, this does not preclude other cities from having high-quality festivals as well. But as they may well be aware, they are not likely to supplant the famous Renaissance centres.
Keywords: umetniški festivali; umetnost; art; culture; kultura; množična kultura; občinstvo